EFEKTIVITAS MEDIA PEMBELAJARAN E-COMIC PADA MATA PELAJARAN FIQH KELAS VIII - Kurniawan, Bayu; Marwan, Iwan; Manan, Abdul (Edudeena : Journal of Islamic Religious Education, 2017)
Abtract: Teaching media in relation of teaching and learning process in school, can enhance the learning process of students in teaching which in turn is expected to enhance the learning achievement. This study intends to find out whether there is a significant influence to the students through the e-comic teaching media and to know the effectiveness of the application of this media so as to improve student learning outcomes in MTs Negeri Grogol.The population of this research are 348 students of Grade VIII MTs Negeri Grogol, Kediri Regency which is divided into eight classes. While the number of samples in this study are 84 students of class VIII-A and VIII-B. Sampling was determined by random sampling technique. The result of experimental quantitative research reveals that learning with the use of e-comic learning media is more effective than the teaching and learning process without using instructional media on the subject of halal and haram food and beverages in Grade VIII MTs Negeri Grogol. The group treated using e-comic learning media has an average value of 75.05. While the group that is not treated or using the conventional method has an average value of 68.48. Abstrak: Media pengajaran dalam kaitannya dengan proses belajar mengajar di sekolah, dapat mempertinggi proses belajar siswa dalam pengajaran yang pada gilirannya diharapkan dapat mempertinggi hasil belajar yang dicapainya. Penelitian ini bermaksud untuk mengetahui apakah ada pengaruh yang signifikan kepada siswa melalui media pengajaran e-comicdan mengetahui efektivitas penerapan media ini sehingga dapat meningkatkan hasil belajar siswa di MTs Negeri Grogol. Populasi penelitian ini adalah 348 siswa kelas VIII MTs Negeri Grogol, Kabupaten Kediri yang terbagi menjadi delapan kelas. Sedangkan jumlah sampel dalam penelitian ini sebanyak 84 siswa kelas VIII-A dan VIII-B. Pengambilan sampel ditentukan dengan teknik random sampling. Hasil penelitian kuantitatif eksperimental mengungkapkan bahwa pembelajaran dengan penggunaan media pembelajaran e-comic lebih efektif dibandingkan dengan proses belajar mengajar tanpa menggunakan media pembelajaran pada pokok bahasan makanan dan minuman halal dan haram pada kelas VIII MTs Negeri Grogol. Kelompok yang diberi perlakuan dengan menggunakan media pembelajaran e-comic mempunyai rata-rata nilai sebesar 75,05. Sedangkan kelompok yang tidak diberi perlakuan atau yang menggunakan metode ceramah mempunyai rata-rata sebesar 68,48.